Penerimaan Zakat dan Penurunan Kemiskinan di Aceh: Peran Dana Otonomi Khusus Sebagai Pemoderasi - Muliadi Muliadi; Khairul Amri (ITB AAS INDONESIA Surakarta, 2019)
This study aims to analyze the effect of the zakat revenue on poverty by using the special autonomy fund (DOK) as a moderating variable. Using panel data of 15 districts from Aceh province from 2011 to 2016, Moderated Regression Analysis (MRA) was used to analyze the functional relationship. The study found that zakat revenue and DOK had a negative and significant effect on poverty reduction. The negative impact of DOK on poverty partially more significant compared to the negative impact of zakat revenue. The existence of DOK does not only play a role as a predictor variable but also moderates the effect of zakat revenue on poverty reduction in Aceh.